Shafei Inheritance Distribution from Book Manuscript Manhaj al-Wusul ila Tahrir al-Fusul | الفرائض الشافعي من نسخة كتاب منهج الوصول إلى تحرير الفصول - Iin Suryaningsih (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2015)
The study on the book Minhaj wushul ila al-Tahrir al-Fushul is focused on the Islamic inheritance jurisprudence that includes jurisprudence, count and number. With this approach philological sciences, this manuscript can be confirmed as the work of Shaikh Zakaria al-Ansari al-Shafi'i, and from the study revealed wisdom tasyri of different parts (more or less) inheritance, rights related to inheritance, the causes of inheritance and expenditures taken from the estate.